The Effect of eWOM on Consumer Purchase Intention for Richeese Factory in Bandung via TikTok - Jesicca Bella Roberta; Indira Rachmawati (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Social media platforms, particularly TikTok, have transformed how consumers engage with brands, influencing purchase decisions through electronic word-of-mouth. This study aims to investigate the effect of electronic word-of-mouth on consumer purchase intention for Richeese Factory in Bandung, Indonesia, using the Information Adoption Communication Model. Data were collected from 253 TikTok users aged 18–30 years through a survey and analyzed using structural equation modeling with partial least squares in SmartPLS 4.0. The findings reveal that Information Adoption, Credibility, Needs, and Attitudes toward Information significantly influence purchase intention. However, Information Quality does not significantly affect Information Usefulness, indicating that consumers prioritize engaging and credible content over detailed information. The model’s marginal fit, with a Normed Fit Index of 0.777–0.788, suggests that unmodeled factors, such as algorithmic variability, may be present. This study underscores TikTok’s role in shaping consumer behavior in the fast-food industry, offering practical insights for Richeese Factory to leverage influencer-driven content. Future research should investigate the negative effects of electronic word-of-mouth and cross-cultural influences to improve model fit.